Review of the impact of epidemics on mental and developmental health in parents and children: Examining the effects of epidemic diseases on the well-being of parents and children (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The CDC defines an epidemic as a sudden and unexpected increase in the number of diseasecases in a specific geographic area. Epidemics include diseases like smallpox, measles, and polio, toname just a few. This doesn't mean that an epidemic illness has to be communicable. The outbreaks ofWest Nile fever and obesity are also referred to as epidemics. If a disease or particular health-relatedactivity (e.g., smoking) is clearly above the anticipated prevalence in a community or area, it may beconsidered an epidemic. In this paper discuss the impact of epidemics on mental and developmentalhealth in parents and children.